Analysis of the influence of conscientiousness, personality traits, and dyadic communication on decision-making among women of reproductive age in contraceptive use - Rochmawati Rochmawati; Hera Lestari Mikarsa; Ira Puspitawati (Empathy : Jurnal Fakultas Psikologi, 2025)
Contraceptive decision-making is a complex process influenced by an interplay of psychological characteristics and interpersonal dynamics.  which may contribute to dissatisfaction and discontinuation among users. This study examined the effects of conscientiousness as a personality trait and dyadic communication on the quality of contraceptive decision-making among women of reproductive age. A cross-sectional study design was employed.  involving 186 married women aged 20–50 years who were current contraceptive users.  recruited through purposive sampling. Data were collected using the Big Five Personality Scale (α = 0.82).  the Dyadic Communication Scale (α = 0.89).  and the Decision-Making Scale (α = 0.87). Multiple linear regression analysis demonstrated that conscientiousness (β = 0.563.  p < 0.001) and dyadic communication (β = 0.358.  p < 0.001) were significant predictors of decision-making quality.  collectively accounting for 79.2% of the variance (R² = 0.792). In addition.  significant differences in decision-making quality were identified across age groups.  educational levels.  contraceptive methods.  and employment status. These findings underscore the importance of integrating psychological traits and partner communication into contraceptive counseling strategies to improve informed and satisfactory decision-making among women of reproductive age.